Print hegemony or just a(nother) platform ? : digital first production at daily newspapers - (:unkn) unknown (My University, 2025)
The present thesis is a study of digital first newspapers and their underlying production systems. Digital first represents a neglected research topic within (digital) journalism studies. This research broadly asks the question: How are digital and print versions of newspapers produced? Thanks to an in-depth ethnography at French-language Swiss legacy newspaper Le Temps in 2018 as well as interviews with newsworkers from La Côte, 20 Minutes and Le Temps in 2021, I provide descriptions of how web and print stories are produced at all three newsrooms (including at Le Temps at two different moments in time). I analyze the struggles between digital and analog, many of which play out on the battlefields of space and time. Successfully implementing idealized versions of digital stories (in terms of temporality, content and digital affordances) is subject to being able to untether digital from print, the former often being subjugated to the latter. Achieving this comes at a cost, since it requires what I call a print capacity surplus: having resources to produce and edit stories beyond those required to fill the pages of the print newspaper. I discuss the varying print capacity surpluses of the three newspapers studied and its impact on their digital firstness. Finally, I offer a definition of digital first, which integrates five dimensions: workflow, temporality, mindset, text-level features, and strategy. For heuristic purposes, these are arranged into a digital first matrix, creating bridges for understanding digital and print news production at other newspapers. In terms of method, I mainly borrow from classic inductive ethnography, actor-network theory and newsmaking reconstruction.
Keywords: journalisme; numérique; innovation; newsroom; format; stratégie éditoriale